Cognition improvement strategies, study behaviors and stress among medical students of Dow University of Health Sciences: a cross-sectional study - Jahangeer, Syed Muhammad Ashraf; Muhammad Hamdan; Ansari, Ushna Sunain; Khan, Huzaif Saeed; Rida Fatima (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the effects of cognition improvement strategies on academic performance, stress and sleep quality of medical students. Method: The cross-sectional study was conducted att he Dow University of Health Sciences, Karachi, from March 2019 to March 2020, and comprised medical students regardless of gender and academic year. Academic performance was assessed through grade point average, while stress and sleep were assessed using the Perceived Stress Scale and Pittsburgh Sleep Quality Index. Data was analysed using SPSS 25. Result: Of the 770 subjects, 748(97%) formed the final sample with mean age 20.32±1.49 years; 619(82.7%) females and 129(17.2%) males. Overall, there were 655(87.6%) consumers of cognitive enhancers and 93(12.4%) non-cunsumers. The mean Pittsburgh Sleep Quality Index score of consumers was 6.05±3.306, while that of non-consumers was 5.80±3.701. The respective mean Perceived Stress Scale scores were 21.18±6.09 and 20.5±6.8. There was no significant association of consumption of cognitive enhancers with academic performance and stress levels (p>0.05), but it was significant with sleep quality (p<0.05). Conclusion: Majority of the students were found to be consuming cognitive enhancers, but no significant association of the stimulants was found with either academic performance or stress.